THE EFFECT OF PREZY AND EXE-LEARNING MEDIA ON CHEMICAL LEARNING RESULTS - Roza Linda; Sri Wilda Albeta; Masnaini Masnaini; Sulismawati Sulismawati (EDUSAINS, 2018)
PENGARUH MEDIA PREZI DAN EXE-LEARNING TERHADAP HASIL PEMBELAJARAN KIMIA Abstract Development of information technology in education such as the existance of media that derived from e-learning has made it easier in teaching and learning process. This study aimed to investigate the effectiveness of Prezi and eXe-Learning media in students’activities and their learning outcome. This study used a quasi-experimental design. The research instrument used test questions based on subject of chemistry bonding and molecules with the participants are 72 students from Senior High School in Pekanbaru. The students come from 2 different classes: class used Prezi (36) and class used eXe-Learning media (36). The result showed a significant difference in students’ activities between groups that used Prezi and eXe-Learning media. For learning outcome, there was no any significant difference between student that used prezi and eXe-Learning media.  Abstrak Perkembangan teknologi informasi dalam bidang pendidikan seperti penggunaan media pembelajaran e-learning mempermudah proses belajar mengajar. Penelitian ini bertujuan untuk melihat efektifitas media pembelajaran prezi dan eXe-Learning dalam hal aktivitas belajar dan hasil belajar  peserta didik.  Penelitian ini merupakan jenis penelitian kuasi eksperimen dengan instrumen penelitian berupa soal ujian pada materi pembelajaran ikatan kimia dan bentuk molekul dengan sampel penelitian peserta didik sekolah menengah atas di Pekanbaru sebanyak 72 orang peserta didik yang terdiri dari kelas yang menggunakan media prezi (36) dan media eXe-Learning (36). Hasil analisis didapati perbedaan yang signifikan aktivitas belajar kelas yang menggunakan media prezi dengan media eXe-Learning. Sementara untuk hasil belajar kedua kelas menunjukkan tidak terdapat perbedaan yang signifikan antara kelas yang menggunakan media prezi dengan media eXe-Learning.  Permalink/DOI:http://dx.doi.org/10.15408/es.v10i1.7204